THE ROLE OF ARABIC LANGUAGE TEACHING IN DEVELOPING STUDENTS' LANGUAGE SKILLS AT MTS AISYIYAH TEMBUNG, NORTH SUMATRA - Jumadi, Jumadi; Fahrurrazi, Fahrurrazi (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
This study aims to examine the role of Arabic language learning management in improving students' language skills at Madrasah Aliyah Aisyah (junior high school level). This research used a qualitative approach with a case study method, focusing on the Arabic language learning process at the school. Data were collected through interviews with Arabic language teachers, observations of the learning process, and analysis of curriculum documents and teaching materials. The results indicate that effective learning management, which includes thorough planning, the use of diverse methods, and systematic evaluation, has a positive impact on improving students' language skills. Furthermore, the use of engaging learning media and a contextual approach enriches students' learning experiences. This study concludes that organized and innovative Arabic language learning management plays a significant role in improving students' language competencies at Madrasah Aliyah Aisyah, making it a model worthy of emulation by other educational institutions in managing foreign language teaching.